Die Vorarlberger Textilindustrie im Wandel der 1970er-Jahre bis in die 2000er - Simon Groß (Historia.scribere)
This exposition concerns causes of change of textile industry in Vorarlberg which set in in the seventies and sustained still after the turn of the millennium. Various causes for the decrease and economic difficulties of this industry will be shown, but also the terms „specialization“ and „innovation“ as well as appearance of so called commerce and industry parks are considered as flipsides of the change of the textile industry, these aspects compose the contemporary shape oft the economic structure in Vorarlberg.